2001
DOI: 10.1152/ajpcell.2001.280.4.c943
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of P2X7 nucleotide receptor function in human monocytes by extracellular ions and receptor density

Abstract: P2X receptors function as ATP-gated cation channels. The P2X(7) receptor subtype is distinguished from other P2X family members by a very low affinity for extracellular ATP (millimolar EC50) and its ability to trigger induction of nonselective pores on repeated or prolonged stimulation. Previous studies have indicated that certain P2X(7) receptor-positive cell types, such as human blood monocytes and murine thymocytes, lack this pore-forming response. In the present study we compared pore formation in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 43 publications
(51 reference statements)
10
104
0
Order By: Relevance
“…Furthermore, monocytes further increase the numbers of surface receptors as they differentiate into macrophages [4]. Flow cytometry of fresh human monocytes, gating on the CD14 monocyte marker, reveals that both baseline and LPS-treated monocytes have similar levels of surface expressed P2X 7 [5] confirming previous data showing expression on 1-day-old monocytes [6].…”
Section: Human Monocytes Express P2x 7 Receptorssupporting
confidence: 81%
“…Furthermore, monocytes further increase the numbers of surface receptors as they differentiate into macrophages [4]. Flow cytometry of fresh human monocytes, gating on the CD14 monocyte marker, reveals that both baseline and LPS-treated monocytes have similar levels of surface expressed P2X 7 [5] confirming previous data showing expression on 1-day-old monocytes [6].…”
Section: Human Monocytes Express P2x 7 Receptorssupporting
confidence: 81%
“…In line with their data, we also observed that these ionic conditions resulted in an increased agonist affinity, such that 100 μM ATP was sufficient for the activation of a nonselective pore by P2X 7 receptors. Although it is not known why ATP induces a pore in macrophages and not in monocytes in normal NaCl-containing medium, the number of cell surface P2X 7 receptors, which is significantly higher in macrophages than in monocytes, seems to play a critical role [37]. To our surprise, NAD + , in contrast to ATP, failed to induce the nonselective pore that typifies activated P2X 7 receptors.…”
Section: Engagement Of P2x 4 Receptorsmentioning
confidence: 54%
“…However as described earlier, monocytes, in contrast to monocyte-derived macrophages, do not form pores in [46,47]. Considering the crucial role of ionic compositions of the extracellular medium in P2X 7 receptor activation by ATP [48][49][50][51], Gudipaty et al [37] showed that replacement of extracellular Na + and Cl − with K + and nonhalide anions strongly facilitated ATP-dependent pore formation in monocytes. In line with their data, we also observed that these ionic conditions resulted in an increased agonist affinity, such that 100 μM ATP was sufficient for the activation of a nonselective pore by P2X 7 receptors.…”
Section: Engagement Of P2x 4 Receptorsmentioning
confidence: 88%
See 1 more Smart Citation
“…Additional studies are needed to examine whether expression of P2X7 is regulated and how such regulation might contribute to bone cell function. In this regard, exposure to certain stimuli has been found to enhance P2X7 expression in various cell types [89][90][91]. On the other hand, high concentrations of ATP appear to mediate internalization of P2X7 in osteoclast-like cells [59].…”
Section: Prospects and Conclusionmentioning
confidence: 99%